Dissolved organic carbon (DOC) is essential to balance the metabolic demands of four dominant North‐Atlantic deep‐sea sponges. Issue 3 (7th December 2020) - Bart, Martijn C.; Mueller, Benjamin; Rombouts, Titus; van de Ven, Clea; Tompkins, Gabrielle J.; Osinga, Ronald; Brussaard, Corina P.D.; MacDonald, Barry; Engel, Anja; Rapp, Hans Tore; de Goeij, Jasper M.
Abstract: Sponges are ubiquitous components of various deep‐sea habitats, including cold water coral reefs, and form deep‐sea sponge grounds. Although the deep sea is generally considered to be a food‐limited environment, these ecosystems are known to be hotspots of biodiversity and carbon cycling. To assess the role of sponges in the carbon cycling of deep‐sea ecosystems, we studied the carbon budgets of six dominant deep‐sea sponges of different phylogenetic origin, with various growth forms and hosting distinct associated microbial communities, in an ex situ aquarium setup. Additionally, we determined biomass metrics—planar surface area, volume, wet weight, dry weight (DW), ash‐free dry weight, and organic carbon (C) content—and conversion factors for all species. Oxygen (O2 ) removal rates averaged 3.3 ± 2.8 μ mol O2 g DWsponge h −1 (mean ± SD), live particulate (bacterio‐ and phytoplankton) organic carbon removal rates averaged 0.30 ± 0.39  μ mol C g DWsponge h −1 and dissolved organic carbon (DOC) removal rates averaged 18.70 ± 25.02  μ mol C g DWsponge h −1 . Carbon mass balances were calculated for four species and revealed that the sponges acquired 1.3–6.6 times the amount of carbon needed to sustain their minimal respiratory demands. These results indicate that irrespective of taxonomic class, growth form, and abundance of microbial symbionts, DOC is responsible for over 90% of the total net organic carbon removal of deep‐sea sponges and allows them to sustain themselves in otherwise food‐limited environments on the ocean floor.